Stateswomen : A Centennial History of Arkansas Women Legislators, 1922-2022 - Smith, Lindsley Armstrong, 1963-; Smith, Stephen A., 1949- (Book collections on Project MUSE., 2022)
"Stateswomen celebrates the centennial of women serving as members of the Arkansas General Assembly. The book features concise biographies of all the women legislators who have served in the assembly to date, situating their political activity within the history of the expansion of the role of women in the public sphere"--